Reviewing hemangiomas and vascular malformations: An in-depth analysis - Zaki Sayyed; Yashmin Parveen; Antara Bhattacharyya; Ansari Mohd Arshiyan; Ahtesham Shah; Krutika Bidkar (Wolters Kluwer Medknow Publications, 2024)
This narrative review delves into the intricacies of hemangiomas and vascular malformations (VMs), exploring their characteristics, diagnostic approaches, and therapeutic interventions. Hemangiomas, characterized by an abnormal growth of blood vessels, and VMs, arising from developmental abnormalities in blood vessels, present multifaceted challenges in clinical practice. The review navigates through the clinical manifestations and classifications of these vascular anomalies, emphasizing the importance of accurate diagnosis based on clinical evaluation, imaging techniques, and histopathological assessment. Variations in presentation, ranging from asymptomatic lesions to severe complications impacting vital organs, underscore the necessity for comprehensive understanding and tailored management strategies. Moreover, this review examines current therapeutic modalities encompassing medical, interventional, and surgical interventions. It synthesizes the evolving landscape of treatment options and highlighting the benefits, limitations, and potential adverse effects associated with each approach. In addition, the review underscores the significance of a multidisciplinary approach, integrating expertise from dermatology, radiology, and surgery, to optimize patient care and outcomes. The challenges posed by these vascular anomalies necessitate ongoing research endeavors aimed at refining diagnostic criteria and advancing therapeutic innovations. This review amalgamates existing knowledge and providing clinicians and researchers with a comprehensive understanding of hemangiomas and VMs, thereby fostering continued exploration and innovation in this complex field.